100 % Digital in der Prozessindustrie – Eindrücke und Ergebnisse vom Tutzing‐Symposion 2018. Issue 11 (27th September 2018) - Kockmann, Norbert
Abstract: In April 2018, nearly 100 experts and decision makers discussed in Tutzing the effects of digital tools in the process industry. Based on the persona concept, various prototypes were developed with elements of design thinking in the workshops and summarized in 12 theses. The close data network within the entire value chain as well as the product and process development is supported by the digital twin as well as different methods of artificial intelligence.